2019
DOI: 10.3390/w11030411
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Water and Technology—Competing Expectations and Confronting Knowledges in the Case of the Coca Codo Sinclair in Ecuador

Abstract: Recent and on-going mega-hydraulic development in the global South implies profound socio-technical, ecological, territorial and cultural transformations at different levels and spaces of society. The transformations often involve conflicts and also new governance arrangements between different knowledge regimes, local practices and national and global frameworks of climate mitigation, water resources management and the green economy. Significantly, they also entail varying expectations concerning the meaning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…"A range of powerful, transnationally allied groups and organizations have historically promoted the construction of these projects: politicians, bureaucrats, landed classes, and industrialists, multinational corporations, the World Bank, and other international organizations, as well as transnational professional associations of engineers and scientists" [7] (p. 3), which he calls an informal international "big dam regime". Underlying this regime are the deeply rooted values, norms and principles that, together, have promoted a development vision that was conceptualized nearly a century ago and which has been unleashed since the 1950s and 1960s (see, in this issue [8][9][10][11][12][13][14][15][16][17]). This vision equated development as the largescale, top-down, techno-centric pursuit of economic growth through the intensive exploitation of natural resources, that commonly disregards alternative knowledge systems, development trajectories and human suffering.…”
Section: Mega-hydraulic Dams Socioenvironmental Impacts and Knowledgmentioning
confidence: 99%
See 3 more Smart Citations
“…"A range of powerful, transnationally allied groups and organizations have historically promoted the construction of these projects: politicians, bureaucrats, landed classes, and industrialists, multinational corporations, the World Bank, and other international organizations, as well as transnational professional associations of engineers and scientists" [7] (p. 3), which he calls an informal international "big dam regime". Underlying this regime are the deeply rooted values, norms and principles that, together, have promoted a development vision that was conceptualized nearly a century ago and which has been unleashed since the 1950s and 1960s (see, in this issue [8][9][10][11][12][13][14][15][16][17]). This vision equated development as the largescale, top-down, techno-centric pursuit of economic growth through the intensive exploitation of natural resources, that commonly disregards alternative knowledge systems, development trajectories and human suffering.…”
Section: Mega-hydraulic Dams Socioenvironmental Impacts and Knowledgmentioning
confidence: 99%
“…Hydropower and other mega-hydraulic projects have long been a deeply controversial issue, generating intense local, national and transnational disputes among proponents and opponents. Large-scale water infrastructure development has been shown to generate profound social and environmental impacts, the more so since the burdens and benefits are unevenly distributed among population groups and locations [8][9][10][11][12][13][14][15][16][17]. Commonly, mega-hydraulic projects aim to supply water and/or energy to industrial growth sectors, large-scale capitalist export agriculture, and the growing thirst of mega-cities and urban zones [18,19].…”
Section: The Return Of Mega-hydraulics: Modernity and Control Over Namentioning
confidence: 99%
See 2 more Smart Citations
“…However, from our examination, we concluded that the popular interest in and defense of the project did not result in a more protective stand towards affected host communities. Similar to the position and actions of dominant mega-hydraulic proponents in other cases around the world (e.g., [18][19][20][21][22][23][24][25][26]), the popular supporters (city inhabitants and valley peasants) ignored the fate of the affected highland indigenous communities.…”
Section: The Misicuni Multipurpose Projectmentioning
confidence: 95%